Are proximal and distal neuromuscular parameters able to predict hip and knee frontal plane kinematics during single-leg landing?. (January 2023) - Rodrigues, Rodrigo; Gonçalves, Vagner; Casagrande, Rafael; Cemin, Fabrício; Nodari, Camila; Borges, Iury; Fitarelli, Luan; Bianchesse, Jean; Rocha, Emmanuel Souza da; Rabello, Rodrigo
Abstract: Objective: To determine if proximal and distal neuromuscular parameters (EMG amplitude and median frequency – MDF) can predict frontal plane kinematics during single-leg landing. Study design: Cross sectional study. Setting: Laboratory. Participants: Fifteen participants (7 female) performed six single-leg landings with measures of frontal plane kinematics and EMG obtained 230 ms after first foot contact, totalizing 90 landings. Main outcome measures: (i) 2D hip adduction [hip ADD] and knee frontal plane projection angle [knee FPPA]; (ii) EMG amplitude and MDF of gluteus medius [GMed], tensor fascia latae [TFL], peroneus longus [PL] and tibialis anterior [TA]. Results: We observed that MDF of TA was a significant predictor of hip ADD (p = 0.037; β = −0.049 Hz; R 2 c = 0.30). Also, MDF of PL was significant predictor of knee FPPA (p = 0.043; β = 0.042 Hz; R 2 c = 0.37). Hip muscles and EMG amplitude parameters were not considered predictors of frontal plane kinematics. Conclusion: The firing frequency of ankle muscles predicted the variance of hip and knee frontal plane kinematics during single-leg landing. Highlights: EMG parameters of hip abductors were not associated with frontal plane kinematics. Lower firing frequency of tibialis anterior was associated with higher hip adduction. Higher firing frequency of peroneus longus was associated with higher knee valgus.